2021
DOI: 10.1108/ijsi-10-2021-0108
|View full text |Cite
|
Sign up to set email alerts
|

High-cycle and very-high-cycle fatigue behavior of a stainless steel for air-conditioning compressor valve plates

Abstract: PurposeThe investigations could guide the structural design and fatigue life prediction of air-conditioning compressor valve plates.Design/methodology/approachThe High-Cycle Fatigue (HCF) and Very-High-Cycle Fatigue (VHCF) behaviors of stainless steel used for air-conditioning compressor valve plates were investigated. Monotonic and cyclic loading conditions were designed to explore the fatigue responses according to the load characteristics of the structure.FindingsThe crack initiation can be observed as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Moreover, due to the increased lifetime of components, experimental investigations of fatigue responses should focus also on the very high cycle fatigue (VHCF, N > 10 7 ) life range with low-amplitude loads [44,45] applied for a long time or with a high frequency, e.g., those due to vibrations. For example, in recent years, VHCF tests have been carried out to investigate a wide set of materials such as stainless steel [46], steels produced with different processes [47], steels with large risk volume [48], and adhesively bonded joints [49,50], confirming the industrial and academic interest towards this research field. Particular attention has also been paid to the quantification of the influence of stress singularities on the joint life [43], size effects [51], and, in general, the fatigue responses of adhesives under the VHCF regime.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, due to the increased lifetime of components, experimental investigations of fatigue responses should focus also on the very high cycle fatigue (VHCF, N > 10 7 ) life range with low-amplitude loads [44,45] applied for a long time or with a high frequency, e.g., those due to vibrations. For example, in recent years, VHCF tests have been carried out to investigate a wide set of materials such as stainless steel [46], steels produced with different processes [47], steels with large risk volume [48], and adhesively bonded joints [49,50], confirming the industrial and academic interest towards this research field. Particular attention has also been paid to the quantification of the influence of stress singularities on the joint life [43], size effects [51], and, in general, the fatigue responses of adhesives under the VHCF regime.…”
Section: Introductionmentioning
confidence: 91%
“…However, this simplification not only affects the blade's natural frequencies but also the vibration stresses, which may lead to deviations of high cycle fatigue (HCF) properties and induce a risk to the engine's safety (Li et al ., 2022, 2023a, b; Deng et al ., 2022; Liao et al ., 2022; Luo et al ., 2022a, b, 2023; Jia et al ., 2022; Zhu et al ., 2017). Studies (Wu and Guangchen, 2015) have revealed that increasing number of film cooling holes could reduce a specific value of the blade's natural frequency by up to 8.0%.…”
Section: Introductionmentioning
confidence: 99%
“…The current research on fatigue life is mainly divided into fatigue life research in the low cycle fatigue stage (number of stress cycles at material failure less than or equal to 10 5 ) and high cycle fatigue stage (number of stress cycles at material failure more than 10 5 ). [1][2][3][4] The fatigue life prediction, [5][6][7][8][9] fatigue damage mechanism, [10][11][12][13] and the influence of material manufacturing process on fatigue performance 14,15 for various materials have been a hot topic of research. The fatigue of mechanical components has also been a valuable topic.…”
Section: Introductionmentioning
confidence: 99%